2021
DOI: 10.3390/fermentation7010006
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in Biological Conversion of Industrial Hemp for Biofuel and Value-Added Products

Abstract: Sustainable, economically feasible, and green resources for energy and chemical products have people’s attention due to global energy demand and environmental issues. Last several decades, diverse lignocellulosic biomass has been studied for the production of biofuels and biochemicals. Industrial hemp has great market potential with its versatile applications. With the increase of the hemp-related markets with hemp seed, hemp oil, and fiber, the importance of hemp biomass utilization has also been emphasized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 76 publications
(130 reference statements)
1
14
0
Order By: Relevance
“…However, no literature on aqueous, acid, and alkali pretreatment of flaxseed meal were found. Similar results have been reported by Ji et al, who observed that the cellulose content (72.4%) of acid pretreated hemp biomass was increased than untreated hemp biomass [48]. According to Qi et al, chemical pretreatment of bamboo using acid and alkali exhibited the highest cellulose content and lowest lignin and extractive content [49].…”
Section: Pretreatments Of Flaxseed Mealsupporting
confidence: 86%
“…However, no literature on aqueous, acid, and alkali pretreatment of flaxseed meal were found. Similar results have been reported by Ji et al, who observed that the cellulose content (72.4%) of acid pretreated hemp biomass was increased than untreated hemp biomass [48]. According to Qi et al, chemical pretreatment of bamboo using acid and alkali exhibited the highest cellulose content and lowest lignin and extractive content [49].…”
Section: Pretreatments Of Flaxseed Mealsupporting
confidence: 86%
“…Hemp biomass is primarily composed of cellulose, hemicellulose, and lignin with ash and extractives. 8 High polysaccharide (30–50% of cellulose and 10–20% of hemicellulose) contents in hemp plants are comparable to those in other herbaceous or woody plants. A comparison of hemp with common lignocellulosic biomass types is summarized in Table 1A .…”
Section: Introductionmentioning
confidence: 92%
“…The chemical composition of the different herbaceous and oilseed crops is presented in Table 1, for easier comparison between them. (2)(3)(4), palmitic (4-7), linoleic (35)(36)(37)(38)(39)(40), oleic (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), and α-linolenic ] Miscanthus × giganteus [6,29] ( As can be seen in Table 1, species such as cardoon and linseed have the potential for biodiesel production since oil can be obtained from the seeds. Another species that also has this characteristic, despite not being specified in the table, is hemp, as oil can also be obtained from the seed.…”
Section: Herbaceous and Other Cropsmentioning
confidence: 99%